共同希望语言学院强化班效率分析 - Dewi Verensia Tanery (Sinolingua: Journal of Chinese Studies, 2025)
Learning efficiency as an indicator of learning pace. The improvement of students' learning efficiency is a goal cherished by every teacher and highly anticipated by both students and their parents. In the context of universal education, intensive classes provide students an opportunity to review classroom knowledge, revisit unfamiliar or poorly understood concepts, and master and apply them effectively. The Common Hope Language Institute has established "intensive class" to offer a learning platform for students who perform poorly in exams or experience a decline in academic performance. These classes aim to enhance the learning abilities and efficiency of struggling students. Given the limited time available to acquire a solid foundation in Chinese and achieve good exam results, learning efficiency becomes particularly critical. This study investigates and summarizes the effectiveness of the intensive classes at the Common Hope Language Institute. Findings suggest that these classes help students gain a more comprehensive understanding of classroom knowledge, consolidate what they have learned, and help them to solve their learning difficulties.